2007
DOI: 10.1002/dys.357
|View full text |Cite
|
Sign up to set email alerts
|

Phonological working memory in German children with poor reading and spelling abilities

Abstract: Deficits in verbal short-term memory have been identified as one factor underlying reading and spelling disorders. However, the nature of this deficit is still unclear. It has been proposed that poor readers make less use of phonological coding, especially if the task can be solved through visual strategies. In the framework of Baddeley's phonological loop model, this study examined serial recall performance in German second-grade children with poor vs good reading and spelling abilities. Children were present… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
26
1
4

Year Published

2009
2009
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(35 citation statements)
references
References 64 publications
4
26
1
4
Order By: Relevance
“…Some researchers have observed that the deficit appeared to be specific to the store mechanism (a reduced phonological similarity effect; i.e., rhyming items are more difficult to remember than non-rhyming items), while the subvocal rehearsal mechanism remained intact. However, others have found that children with DD exhibited less-efficient rehearsal processes (a reduced word length effect; i.e., short words are easier to remember than sequences of long words) or that phonological similarity and word length effects did not differ between children with DD and typical readers (TR) (Kibby, 2009;Pickering, 2004;Steinbrink & Klatte, 2008). Moreover, some researchers have found an association between PL and articulatory/speech rate (i.e., the number of verbal items repeated per second), suggesting that children with DD experience PL impairments due to their slow articulation rates, which cause the PL to function less efficiently (Kibby, 2009;McDougall & Donohoe, 2002).…”
Section: Working Memory Impairments In Developmental Dyslexiamentioning
confidence: 99%
See 1 more Smart Citation
“…Some researchers have observed that the deficit appeared to be specific to the store mechanism (a reduced phonological similarity effect; i.e., rhyming items are more difficult to remember than non-rhyming items), while the subvocal rehearsal mechanism remained intact. However, others have found that children with DD exhibited less-efficient rehearsal processes (a reduced word length effect; i.e., short words are easier to remember than sequences of long words) or that phonological similarity and word length effects did not differ between children with DD and typical readers (TR) (Kibby, 2009;Pickering, 2004;Steinbrink & Klatte, 2008). Moreover, some researchers have found an association between PL and articulatory/speech rate (i.e., the number of verbal items repeated per second), suggesting that children with DD experience PL impairments due to their slow articulation rates, which cause the PL to function less efficiently (Kibby, 2009;McDougall & Donohoe, 2002).…”
Section: Working Memory Impairments In Developmental Dyslexiamentioning
confidence: 99%
“…Compared to reading, the number of studies exploring the relationship between WM and spelling is clearly limited (some exceptions: Service & Turpeinen, 2001;Steinbrink & Klatte, 2008). As Savage et al (2007, p. 202) noted, this is surprising because "early spelling might -21 -thus be expected to tap central executive and phonological loop resources to a greater degree than in early word reading".…”
Section: Predictive Effect Of Working Memory On Reading and Spelling mentioning
confidence: 99%
“…For example, in a longitudinal study of Finnish, a highly transparent orthography, preschool PM modestly predicted word recognition in Grades 1 and 2, and was strongly related to listening comprehension (Dufva, Niemi, & Voeten, 2001). In a study of word recognition in German speaking second graders, deficits in PM differentiated poor readers from good readers (Steinbrink & Klatte, 2008). In all of the studies, PM was a weaker predictor of early word recognition than was PA.…”
Section: Introductionmentioning
confidence: 99%
“…For the reading process to occur it is necessary for the child to acquire some skills. These skills include language, attention to understand and interpret written language, auditory memory, visual memory, word identification, structural analysis and context of language, logic synthesis, expansion of vocabulary, comprehension and fluency in reading (5)(6)(7)(8) .…”
Section: Introductionmentioning
confidence: 99%